The effects of laurel (Laurus nobilis L.) leaf powder supplementation on performance, carcass characteristics, meat lipid oxidation and some blood parameters of broiler chicks - Arslan Duru, A; Gölcü, AO (Journal of the Hellenic Veterinary Medical Society, 2023)
The purpose of this study was conducted to evaluated the effects of bay laurel (Laurus nobilis L.) leaves powder (LLP) on performance, thigh and breast meat lipid oxidation and chemical composition, body components, digestive tract parts and some blood parameters in broiler chickens. A total of 144 d-old mix-sexed chicks were weighed and randomly assigned to four experimental groups with three replicates of 12 chicks (6 ♀and 6 ♂) each. Treatments were as follows: (i) basal diet-no additive (control), (ii) basal diet+1000 mg/kg LLP, (iii) basal diet+5000 mg/kg LLP and (iv) basal diet+10000 mg/kg LLP. The results revealed that over entire the experimental period body weight and body weight gain increased by LLP supplementation (P<0.01). Feed intake of birds enhanced (P<0.05) whilst feed conversion ratio and chemical composition thigh meat were not significant affected by LLP concentration (P>0.05). Liver improved with 10000 mg/kg LLP (P<0.001) and the weight of ileum + jejunum improved with 5000 and 10000 mg/kg LLP (P<0.01). Breast dry matter (P<0.05), glucose (P<0.05) and with LLP treatment, the TBARS values of breast and thigh meat decreased (P<0.001). As a result, LLP supplementation in broiler diets can be advised because it lowers lipid oxidation in the meat.